Response of rural cattle to Artificial Insemination in Jharkhand - Pandey, A K; Singh, M P; Bansal, S K; Gokhale, S B (Indian Journal of Dairy Science, 2016)
The study was conducted in rural areas of Jharkhand with objectives of evaluating factors affecting the efficiency of Artificial Insemination (A.I.) under farmer’s situation so that effective implementation of A.I. services can be ensured to the farmers. The overall conception rate (C.R.) attained in the study was 53% which is better than the national average conception rate reported So far. The overall conception rate varied with the breed of cattle (P